On 2-Nilpotent loops of 2 generators of exponent 2 - Sabinina Liudmila (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Loops are similar to groups but without associativity. In our talk we will give a classification of loops of two generators of exponent 2 and of class of nilpotency 2. We will discuss the properties of these loops and will give examples. The talk is based on a joint research with M. Rasskazova and A. Grishkov.
Keywords: 2-Nilpotent; generators of exponent 2